Clays and Clay Minerals, Vol. 58, No. 2, 220–237, 2010. - Churchman, Gordon Jock; Pontifex, Ian Russell; Mcclure, Stuart Gerrand (The Clay Minerals Society, 2010)
The occurrenceof halloysite and/or kaolinitein clay-rich, vein-likezone s in saprolites in Hong Kong has provided theopportunit y to examinetheconditions determining theformation of onekaolin mineral or the other and also the nature of their particles. Clay-rich zones within tuffaceous or granitic saprolites from six different hillside sites have been examined in replicate samples by optical and scanning electron microscopy, X-ray diffraction, and thermal analysis. Kaolin minerals, sometimes together with Mn oxides and Fe oxides/oxyhydroxides, have formed within discontinuities within the altered host rocks. The fabrics of kaolin infills generally indicated several generations of kaolin formation and that shear and deformation have commonly occurred within the infills. The infills were either light or dark in color. Lightcolored infills often comprised pure, or nearly pure, halloysite or kaolinite. Dark Mn- and Fe-rich infills all contained kaolinite, while including some halloysite. The very halloysitic, light-colored infills occurred in saprolites in both granite and tuff as long tubular shapes in parallel bunches. The light-colored, very kaolinitic infills occurred in tuff only, in large platy or near-platy shapes within vermiform packets. In dark-colored infills, early kaolin mineral crystallization was limited by impurities from the breakdown of primary minerals leaving dissolved and re-precipitated compounds of Mn and Fe within the infill. Kaolin minerals in infill at all the sites except one are considered to have formed as a result of weathering. The exception comprises white infills in tuff that are composed of extremely small, closely packed particles, suggesting formation by hydrothermal action. Generally, the kaolin minerals have formed by neogenesis out of solution in the discontinuities. Drying, with the formation of Mn and/or Fe oxides/oxyhydroxides, had occurred several times, indicating enhanced drainage. Where drying had occurred, kaolinite had formed. Where indications of drying in infills were absent, halloysite was predominant.
Factors Influencing The Formation And Characteristics Of Halloysites Or Kaolinites In Granitic And Tuffaceous Saprolites In Hong Kong
gsccm58207-chu.pdf -- 3,298KB
Keywords: Periodicals; Geology; Fe Oxides/Oxyhydroxides; Infills; Mn Oxides; Rock Deformation; Shearing; Todorokite; Weathering